One Health: navigating plague in Madagascar amidst COVID-19 - Ritik Agrawal; Jogesh Murmu; Sweta Pattnaik; Srikanta Kanungo; Sanghamitra Pati (BMC, 2023)
Abstract Background Africa sees the surge of plague cases in recent decades, with hotspots in the Democratic Republic of Congo, Madagascar, and Peru. A rodent-borne scourge, the bacterial infection known as plague is transmitted to humans via the sneaky bites of fleas, caused by Yersinia pestis. Bubonic plague has a case fatality rate of 20.8% with treatment, but in places such as Madagascar the mortality rate can increase to 40-70% without treatment. Main text Tragedy strikes in the Ambohidratrimo district as three lives are claimed by the plague outbreak and three more fight for survival in the hospitals, including one man in critical condition, from the Ambohimiadana, Antsaharasty, and Ampanotokana communes, bringing the total plague victims in the area to a grim to five. Presently, the biggest concern is the potential plague spread among humans during the ongoing COVID-19 pandemic. Effective disease control can be achieved through training and empowering local leaders and healthcare providers in rural areas, implementing strategies to reduce human-rodent interactions, promoting water, sanitation and hygiene practices (WASH) practices, and carrying out robust vector, reservoir and pest control, diversified animal surveillance along with human surveillance should be done to more extensively to fill the lacunae of knowledge regarding the animal to human transmission. The lack of diagnostic laboratories equipped represents a major hurdle in the early detection of plague in rural areas. To effectively combat plague, these tests must be made more widely available. Additionally, raising awareness among the general population through various means such as campaigns, posters and social media about the signs, symptoms, prevention, and infection control during funerals would greatly decrease the number of cases. Furthermore, healthcare professionals should be trained on the latest methods of identifying cases, controlling infections and protecting themselves from the disease. Conclusions Despite being endemic to Madagascar, the outbreak's pace is unparalleled, and it may spread to non-endemic areas. The utilization of a One Health strategy that encompasses various disciplines is crucial for minimizing catastrophe risk, antibiotic resistance, and outbreak readiness. Collaboration across sectors and proper planning ensures efficient and consistent communication, risk management, and credibility during disease outbreaks. Graphical Abstract